Globalisation in Swedish rural areas: organisation of adult education and transitions to work for immigrants in times of depopulation. (20th October 2022) - Rosvall, Per-Åke; Carlbaum, Sara; Benerdal, Malin
ABSTRACT: This article focuses on how local institutions in three rural areas in Sweden organised education and work to assist adult immigrants' integration. We particularly analyse how local officials in educational institutions, employment offices and local governments attempted to support adult immigrants' education-to-work transitions, using a theoretical framework rooted in the ecology of equity concepts. The results show that national policy is oriented towards areas that have larger populations than most rural areas. However, flexible solutions such as finding suitable workplace placements to assist specific immigrants' transitions and integration are sometimes easier in rural areas with closer interactions.